(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the role of reading strategies as a key component in the development of students’ reading proficiency. Although reading comprehension strategies are widely recognized as essential for successful reading, many teachers do not possess a sufficiently strong methodological foundation for teaching them effectively. As a result, learners often struggle to apply appropriate strategies when working with complex academic texts, particularly in high-stakes examinations such as IELTS. To address this issue, the article emphasizes the importance of teacher preparation in developing, selecting, and systematically teaching effective reading comprehension strategies. It explores a range of practical techniques aimed at enhancing learners’ ability to understand, analyze, and interpret texts commonly encountered in IELTS reading tasks. By focusing on strategy-based instruction, this article seeks to support both teachers and learners in improving reading performance and overall outcomes in IELTS classes.